The Variation of Bureaucratic Capacities in the Brazilian Federal Public Administration: an Analysis with Survey Data - Gomide, Alexandre de Avila; Machado, Raphael Amorim; Lins, Rafael da Silva (Organizações & Sociedade, 2022)
This paper aims to demonstrate the variation in bureaucratic capacities within the Brazilian Federal Public Administration concerning organizations belonging to different policy sectors and verify theoretical propositions in the literature about the relationship between the characteristics of public bureaucracy and state action. For such purposes, data from a questionnaire applied to Brazilian federal civil servants were analyzed using a set of multivariate analysis techniques. The findings indicate that organizations with a greater perception of bureaucratic "weberianess" are correlated with innovative organizations and organizational cultures that restrict corruption. Likewise, organizations with greater bureaucratic autonomy are associated with more effective organizations. However, the observed variation between perceived capabilities and performance did not characterize a clearly identifiable pattern of organization type with public policy sectors. In this sense, the article contributes to the literature by adding nuances to the "islands of excellence" approach by verifying that the asymmetry of capabilities within the Brazilian executive branch is more complex than indicated by previous research.